Changes In Organic Matter Content And Chemical Properties Of Durian Series Soil After Conversion Of A Jungle To An Oil Palm Plantation - Hassan, Mohd Sabri (2007)

(untitled)
Oil palm activities have increased rapidly since the 1980’s. The establishment of the oil palm plantations involves opening up of new areas of forested land, conversion of rubber to oil palm and replanting. It is well established that clearing of jungle for agriculture purpose results in environmental problem, including land degradation, especially in hilly terrains, when terracing is carried for crop cultivation. However, under oil palm cultivation, unlike other crop, the crop management practices involved the additional of empty fruit bunches (EFB) as a mulch and establishment of legume cover crop in the immature stages and placement of pruned fronds in mature phase, which add a lot of organic mater back to the soil to rebuild soil organic matter (SOM) or carbon (C) storage in the soil. Although work has been done to show the benefits of EFB and frond placements and leguminous cover on lowland soils cultivated with oil palm, there are no documented information on the effects of these palm residues on the terraced to show the extent of the addition crop residues (EFB as a mulch, fronds pruned and placement interrows and leguminous establishment) rebuild SOM and rehabilitate the soil. Hypothetically, similar beneficial effects of residues on terraced soil in hilly terrain areas should also be observed. In 1993, a study was initiated at an oil palm plantation at Bukit Rokan, Gemas, Negeri Sembilan, which established after clearing a logged-over jungle in a hilly terrain. The aim was to investigate the long-term in SOM and other related soil chemical characteristics in a hilly terrain. The terraced on hill slope of about 30 degrees. This project was initiated by the Department of Land Management, Faculty of Agriculture, Universiti Putra Malaysia (UPM), in 1993. This study is a continuously of the above with the following: i. to assess the short-term changes (1 year period) of soil organic carbon (SOC) and other related chemical characteristics on a terrace of an 8 ½ year old oil palm area converted from jungle, ii. to determine the long-term (8½ years) changes of SOC and other soil chemical characteristic in the above area, over a period 1993 (under jungle) to 2003 and iii. to compare the SOC content and other soil chemical characteristics of the soil under oil palm in objective ii and soil under jungle in an adjacent jungle area. Since the soil surface cover under the palms is not the same, the establishment of the long term study in 1993, bulk soil sampling was done at three different sites with eight replicated along the terrace around the palm at along the terrace in stratisified random sampling. The area were on upper terrace of hilly area around the base where EFB was earlier applied during the 1st three years, bare soil area – l m radius around outside the palm base and with legumes cover and/or fronds placement between two palms. For the first objective, a short-term study, (1 year) was carried whereby soil samples were taken at three tine interval, i.e. 3rd March 2002, 5th September 2002 and 3rd March 2003 at 0 – 15 cm (topsoil) and 15 -30 cm (subsoil) soil depths. Altogether there were 64 soil samples collected (3 times interval x 3 sites x 2 depth x 8 replication). Soil sample were analysed for total mineral N i.e. (NH4+-N + NO3 --N and NO2 --N), pH (H2O), total N, organic C, light fraction organic matter, available P, exchangeable cations and cation exchange capacity (CEC). There for the second objective, for a long term study, was carried out based on data obtained from the first study from samples collected at 98 and 104 month after planting (MAP) and data from similar soil sampling by previous workers from the time area under jungle, then jungle clearing and planting of palms in a period of about 8½. The third objective was achieved by selecting an adjacent jungle area to the cultivated terraced area in study (ii) as the similar slope. Four terraces were selected in the two cultivated slope and four levels at similar heights of the 4 terraces on two slops under jungle. Bulk topsoil (0 – 15 cm) samples were collected at 8 replicated points above each terrace (under area of oil palm) and level (under area of jungle). Altogether, there was 128 soil sampling [2 main areas (oil palm and jungle) x 4 terrace/level x 2 slopes x 8 replicated point sampling].Results of this study showed dynamic short-term changes in SOC and other chemical characteristics. Small changes or fluctuation in the soil chemical characteristics including SOM occurred that could be attributed to crop management practices and environmental factors. Soil organic carbon, light fraction organic matter, soil pH and CEC of topsoil showed dynamic significant difference between times of sampling under all area of soil cover types (area of EFB apply, bare soil area and area of cover crop). Soil organic carbon for the topsoil, at all soil cover types, showed significant increased until second time sampling but remain similar at third time sampling while at the area of cover crop (Subsoil) showed highly significantly different from first time sampling (0.083%) to third time sampling (1.577%). Soil pH, generally showed significant decreased especially at bare soil and cover crop. Generally, long term-changes study under different area of soil cover types showed fluctuating trend. At the end of this study, at 104 MAP, all soil cover types showed lower values of soil organic carbon (SOC) and other chemical characteristics compared with soil under jungle except for exchangeable potassium. Started from at palm planting until 104 MAP, the build up of SOC and other soil chemical characteristics in this area are about 55 to 65 per cent comparing with soil properties when this sites is under jungle. Study there, showed CEC under jungle area (14.9cmolckg-1) significant high than oil palm (6.5cmolckg-1) while available P showed significant lower than oil palm area. Only exch. Ca and Mg at J2 showed small differences between levels. Generally, it was concluded that short-term study showed dynamic changes of soil properties and fluctuation trend in long-term study. After 8 ½ years SOC and other soil chemical characteristics under oil palm cultivation on terrace still lower than under jungle area but study there showed that not differences soil properties under oil palm and nearby jungle.